SUNFLOW ER-SUMMER LEGUMES INTERCROPPING SYSTEMS UNDER RAINFED CONDITIONS: ECONOMIC ANALYSIS (Biological Sciences - PJSIR, 2002)
Studies pertaining to the economic efficiency of intercropping summer legumes in sunflower under rainfed conditions  were carried out at University of Arid Agriculture, Rawalpindi . Intercropping systems gave higher gross income, net income and benefit cost ratio than the sole cropping of component crops. Amongst the varoius intercropping systems studied, sunflower-mungbean combination proved  to  be  the  best  as  it  gave  the  highest  per  hectare  gross  income  (Rs. 18431.04), net income (Rs.10723.04) and benefit cost ratio (2.39) and it was followed by sunflower-soybean and sunflower-mashbean   intercropping   systems,  respectively.